The beta-turn preferential solution conformation of a tetrapeptide containing an azaamino acid residue - Lee, HJ; Choi, KH; Ahn, IA; Ro, S; Jang, HG; Choi, YS; Lee, KB (ELSEVIER, 2001)
The global minimum energy conformation of an azapeptide model, For-Ala-azaAla-NH2 was predicted by ab initio calculation of the 3-21G and 6-31G* levels. The backbone torsion angle (phi (1), psi (1), phi (2), psi (2)) of an azapeptide model appeared to be the P-turn conformation with a dihedral angle (-61 degrees, 131 degrees, 79 degrees, 15 degrees). This indicates that azaamino acid induces the beta -turn motif regardless of the change of chain length by the addition of an amino acid in azapeptide when compared with the minimum energy conformation of For-azaAla-NH2. We designed and synthesized a tetrapeptide containing azaamino acid, Boc-Ala-Phe-azaLeu-Ala-OMe (1) to verify whether this beta -turn conformation is still conserved in solution. The solution conformation of this azapeptide model was determined by using IR, NMR and molecular modeling techniques. The conformational behavior of this azapeptide was compared with that of the tetrapeptide, Boc-Ala-Phe-Leu-Ala-OMe (2), which was not associated with azaamino acid. The IR evidence of intramolecular H-bonding, the characteristic nuclear Overhauser enhancement (NOE) patterns, the temperature coefficients of amide protons and small solvent accessibility for the azapeptide 1 reveal that it favors the beta -turn structure, whereas the peptide 2 forms extended structure in CDCl3 solution. The average structure of azapeptide I from a restrained molecular dynamics simulation indicated that the dihedral angles [(phi (2), psi (2)), (phi (3), psi (3))] of Phe-azaLeu fragment in a model peptide, Boc-Ala-Phe-azaLeu-Ala-OMe were [(-60 +/- 8 degrees, 125 +/- 24 degrees), (88 +/- 21 degrees, 1 +/- 4 degrees)], and this implies that the intercalation of an azaamino acid residue in tetrapeptide induces the beta II-turn conformation, and the increase of chain length by the addition of an amino acid in azapeptide constituents would not disrupt the backbone dihedral angle of beta -turn conformation. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: X-RAY STRUCTURES; CHEMICAL-SHIFTS; AZA-PEPTIDES; ALANINE; AZAPEPTIDES; TEMPERATURE; AZAPROLINE; INHIBITORS; GLYCINE; COUPLE